The Power of Social Norms: Exploring the Influence of Cultural Factors on Economic Decision-Making - Eny Fahrati (West Science Interdisciplinary Studies, 2023)
This research study aims to explore the influence of social norms and cultural factors on economic decision-making in West Java. By examining the prevalence of social norms, the role of cultural factors, and the alignment of economic behavior with societal expectations, this study highlights the dynamics of economic decision-making in the region. The study utilized a mixed-methods approach, combining a quantitative survey and qualitative interviews to collect data from 400 participants in West Java. The findings of this study highlight the importance of social norms in guiding economic behavior, the influence of cultural factors such as religious beliefs and traditional values, and the challenges and deviations that individuals face in complying with social norms. The results of this study contribute to the existing literature on social norms, cultural factors and economic decision-making, and provide valuable insights for policymakers, businesses and practitioners seeking to promote sustainable economic practices in West Java.